An Exploratory Rasch Model Investigation of Mathematics Anxiety Among Students - Tatan Zenal Mutakin; Munali Munali; Shinta Dewi (STAI Hubbulwathan Duri, 2025)
Mathematics anxiety is a significant barrier to students' academic achievement and engagement with mathematical content. This study aims to explore the key aspects influencing mathematics anxiety among students at various educational levels in Indonesia. An exploratory quantitative approach was employed involving 256 students from elementary, junior high, and senior high schools across West Java, Banten, and the Special Region of Jakarta. Data were collected using a 49-item questionnaire administered via Google Forms. Rasch model analysis was conducted using Winsteps version 4.4.7 to assess item-person fit, followed by inferential statistical analysis using SPSS version 24. After Rasch calibration, 117 student responses and 33 items were deemed valid and reliable for further analysis. The findings identified the attitudinal and psychological aspects as the most influential in contributing to students’ mathematics anxiety. Key indicators included avoidance of mathematics-related tasks, negative perceptions of mathematics, and low self-confidence. Female students, particularly at the junior and senior high school levels, exhibited the highest levels of anxiety. To mitigate mathematics anxiety, it is recommended that educators implement engaging, real-life-based learning approaches, and foster positive beliefs about the role and accessibility of mathematics. Despite its valuable insights, the study is limited by its small, non-random sample and narrow geographic scope. Future research should involve a broader and more diverse population to strengthen generalizability.